2015
DOI: 10.1021/acs.joc.5b00820
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)-Mediated Radical Nitration of Bisarylsulfonyl Hydrazones: Synthesis of Bisarylnitromethyl Sulfones

Abstract: Iron(III)-mediated radical nitration of bisarylsulfonyl hydrazones is described. In this protocol, the nontoxic and inexpensive Fe(NO3)3·9H2O plays a dual role as catalyst as well as nitro source. The mild conditions, broad substrate scope, and the functional group compatibility are the significant features. The reaction pathway has been demonstrated using DFT calculations, and the products can be subsequently converted into oximes using SnCl2·2H2O in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…Based on the above and our previous studies, [9,12,13] a proposed pathway is delineated (Scheme 3). Based on the above and our previous studies, [9,12,13] a proposed pathway is delineated (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above and our previous studies, [9,12,13] a proposed pathway is delineated (Scheme 3). Based on the above and our previous studies, [9,12,13] a proposed pathway is delineated (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…All known compounds were identified by 1 H NMR, 13 C NMR and compared with previously reported data. Reactions were monitored through thin layer chromatography (TLC) on 0.30 mm SiliCycle silica gel plates and visualized under UV light.…”
Section: Methodsmentioning
confidence: 99%
“…Runs 1–3 showed that Fe(NO 3 ) 3 ⋅ 9H 2 O is an effective reagent for the nitration of pyrazolin‐5‐one 1 a at 60–80 °C, but at room temperature 4‐nitropyrazolin‐5‐one 2 a was obtained in a yield of only 33 % (run 4). Apparently, an elevated temperature was necessary for the decomposition of Fe(NO 3 ) 3 ⋅ 9H 2 O and the release of the active nitrating agent NO 2 . The introduction of NaNO 2 into the reaction allowed the room‐temperature nitration of pyrazolin‐5‐one 1 a in high yields (runs 5–7).…”
Section: Resultsmentioning
confidence: 99%
“…A possible reason is the interaction of the solvents and H 2 O with NO 2 , the plausible nitrating reagent generated in situ. In the nonpolar solvent C 2 H 4 Cl 2 , which has previously been widely used in nitration reactions with Fe(NO 3 ) 3 ⋅ 9H 2 O, compound 2 a was obtained in low yield (33 %, run 11), which can be explained by the low solubility of the reagents in this solvent at room temperature. In a number of studies on Fe(NO 3 ) 3 ⋅ 9H 2 O‐mediated nitration, TEMPO proved to be an effective additive to increase the yields of nitro derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation